MICROSTRUCTURAL STUDY OF SYNTHETIC SINTERED DIAMOND AND COMPARISON WITH CARBONADO, A NATURAL POLYCRYSTALLINE DIAMOND - De S.; Heaney P.J.; Fei Y.; Vicenzi E.P. (My University, 2004)
The contributions that Rob Hargraves made to paleomagnetism spanned not only great distances (from the Earth to Mars) but a vast expanse in time. His interests in the magnetic character of the Archean Earth led him to compare magnetic polycrystalline diamonds (stewartites) with non-magnetic diamond composites (carbonados). Rob's ideas inspired our attempt to replicate carbonados by sintering diamond powders without metallic catalysts. These experiments employed a multi-anvil press operating at pressures of 6 to 9 GPa, temperatures of 1200° C to 1800° C, and times up to 6 hours. Transmission electron microscopy (TEM) showed that even in the absence of metals serving as solvent-catalysts, sintered compacts were successfully produced for all runs. In all of these compacts, aperiodic slip planes rigorously parallel to {111} consistently emerged in high densities, with lamellar spacings of 3 to 30 nm. In addition, polysynthetic spinel twinning in close association with the partial slip defects were observed in most of the compacts. Compacts compressed at 8 GPa produced some euhedral crystals with very low dislocation densities surrounded by grains in which dislocation densities were quite high. In addition, curviplanar defects loosely constrained to {111} were visible within some specimens sintered at the highest pressures. These textures resembled defect microstructures observed in natural carbonado (De et al. 1998), and the appearance of these features suggests that our experiments at their most extreme pressure and temperature parameters reproduced carbonado-like defect assemblages.
Keywords: diamond